The test for wrongful arrest of vessels: in search of harmonisation - Goordeen, Sohana (Shipping Law Unit, 2019)
The purpose of this dissertation is to evaluate and analyse the test for the wrongful arrest of vessels and cargo, although my primary focus will be on vessels. My evaluation is geared toward a view that the test is anachronistic, in need of revision and no longer applies effectively in the present day. I will begin by explaining wrongful arrest, and discuss its origins and history, and how the test for wrongful arrest has been applied in various jurisdictions, both common and civil law jurisdictions with a focus on common law judgements. This dissertation also includes reference to the renewed campaign to reform the test for wrongful arrest of vessels, initiated by Professor Mandaraka-Sheppard and debated between Sir Bernard Eder and Martin Davies. I will consider their respective views, supporting justification, arguments in favour and against the reform of the test, as well as possible solutions as to how the test should be reformed. When the test was first established, it was geared to address the challenges of a particular context in time, and now, not only is that context no longer in existence, but the test has created the perhaps unintended consequence of denying potential litigants access to courts, thus creating an inequitable and unjust situation. The work of the International Maritime Committee and the International Working Group on Wrongful Arrest of Vessels, is part of this study, as well as the results of the Questionnaire issued by the International Maritime Committee and the role it seeks to play in achieving harmonisation of the law relating to wrongful arrest. In conclusion, based on the discussion of the issues above, I will affirm my view that the time has come for the revision of the test as it stands in respect of wrongful arrest, and further that this revision should be one that establishes uniformity and harmonisation in this area of the law.